(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2021)
Ethical responsibility is upheld as a strategy that guides the actions of collaborators in institutional management, with rules, values, and norms that contribute to the excellence of their work. Thus, this article analyzes ethical responsibility as a strategy in the humanization of universities. The methodology employed involves an analytical, descriptive, and documentary typology, supported by bibliographic design. As a final reflection, ethical responsibility in universities constitutes an axiological strategy that guides the behavior of individuals in the performance of their activities, contributing to management from a humanized model that adds value to the transparency of academic, research, extension, and administrative processes. These processes facilitate the achievement of indicators for excellence and quality management, which are based on shared morals and values in the workplace.